1986
DOI: 10.1001/jama.1986.03380190066026
|View full text |Cite
|
Sign up to set email alerts
|

Sudden Cardiac Death in Air Force Recruits

Abstract: We reviewed the clinical and autopsy records of the 19 sudden cardiac deaths that occurred among the 1,606,167 US Air Force healthy, medically screened recruits (90% male; 17 to 28 years old) during a 42-day basic training period between 1965 and 1985. Sixteen (all male) died suddenly of underlying structural heart disease, whereas no anatomic cause of death was identified in the remaining three. Thirty-two nonsudden, noncardiac deaths occurred during the same period, and only two had structural heart disease.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
0
1

Year Published

1987
1987
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 184 publications
(29 citation statements)
references
References 19 publications
1
27
0
1
Order By: Relevance
“…One would expect a relatively high prevalence of secondary hypertrophy and hypertrophic cardiomyopathy in elderly patients presenting with diastolic heart failure (19), but the high prevalence of myocarditis in our patient population is somewhat surprising. However, this finding may be explained by 2 facts: first, myocarditis is also known to cause diastolic heart failure (20), which was an inclusion criteria for this study; second, the general prevalence of myocarditis might be underestimated because the clinical diagnosis of myocarditis is often difficult to achieve (21,22). CMRI results.…”
Section: Late Gadolinium Enhancement Versus Endomyocardial Biopsymentioning
confidence: 89%
“…One would expect a relatively high prevalence of secondary hypertrophy and hypertrophic cardiomyopathy in elderly patients presenting with diastolic heart failure (19), but the high prevalence of myocarditis in our patient population is somewhat surprising. However, this finding may be explained by 2 facts: first, myocarditis is also known to cause diastolic heart failure (20), which was an inclusion criteria for this study; second, the general prevalence of myocarditis might be underestimated because the clinical diagnosis of myocarditis is often difficult to achieve (21,22). CMRI results.…”
Section: Late Gadolinium Enhancement Versus Endomyocardial Biopsymentioning
confidence: 89%
“…In previous studies of SUCD, myocarditis was reported infrequently, comprising only 0-30% of all cases (6,11,(13)(14)(15). However, in 1 report on SUCD in US Air Force recruits during a 20-y period ending in 1985 myocarditis was the most common diagnosis, being found in 38% of cases, with a total incidence rate of 0.14:100,000 (9). In 4 of our 16 cases, in addition to myocarditis, changes were noted resembling arrhythmogenic right ventricular cardiomyopathy (ARVC); these changes, however, were observed predominantly in the left ventricle.…”
Section: Introductionmentioning
confidence: 95%
“…In the male ranked elite the number of SUCD cases corresponds to an incidence rate of 10 -100:100,000 person years. This gure is indicative of an increased death rate, as the expected SUCD incidence rate is about 1 case per 100,000 athletes B 35 y of age (3)(4)(5)(6)(7)(8)(9)(10)(11). Between 1974 and 1979, the incidence of SUCD in Sweden in persons 1-20 y old with previously known or unknown cardiac disease was 0.4: 100,000 (12).…”
Section: Introductionmentioning
confidence: 97%
“…About 6 -10% of cases of acute dilated cardiomyopathy are due to myocarditis [7][8][9], and about 20% young adults and athletes present with sudden death as result of myocarditis [10,11].…”
Section: Discussionmentioning
confidence: 99%